Hubungan Antara Sikap Belajar Dengan Keaktifan Belajar Peserta Pelatihan Bahasa Jepang Di LPK Hoshi Hikari Padang - Setiawati, Setiawati; Irwan, Sri Novianti (Jurnal Family Education, 2024)
Abstract This inquire about was spurred by the moo level of movement of preparing members at LPK Hoshi Hikari Padang, this was known from the little number of preparing members who effectively inquired questions and given suppositions within the learning prepare. The point of the inquire about exercises is to decide. The learning demeanors of preparing members; preparing participants' dynamic learning, and; The relationship between learning states of mind and learning activeness of Japanese dialect preparing members at LPK Hoshi Hikari Padang. The research was carried out employing a quantitative approach with a correlational sort. The research population is preparing members who took portion within the Japanese dialect preparing program learning prepare at LPK Hoshi Hikari Padang in 2024. In the interim, the inquire about test was taken employing a cluster inspecting procedure. The inquire about instrument for collecting information employments a survey. Information investigation procedures utilize rate and item minute equations: The investigate comes about appear that: (1) The preparing participants' learning demeanors are categorized as poor; (2) The learning movement of the preparing members is categorized as moo, and (3) There's an awfully noteworthy relationship between the learning demeanor and the learning activeness of the Japanese Dialect preparing members at LPK Hoshi Hikari Padang.